Sulphation Rate in Chandrapur Industrial Cluster, Central India - Kamble, R. K. (International Journal of Environment, 2016)
Sulphation rate in Chandrapur industrial cluster was carried out by using lead peroxide candle turbidimeteric method in December 2014-January 2015 (winter season). Sampling was carried out at four sampling locations; two sampling locations were in upwind direction whereas other two in downwind direction. Minimum sulphation rate in study area was 0.68 mg SO3/100 cm2/day at Tukum, whereas maximum at Ballarpur 1.41 mg SO3/100 cm2/day. Average sulphation rate in study area was 1.12±0.31 mg SO3/100 cm2/day. On comparison of sulphation rate at two road sides, it was observed that at Babupeath–which was adjacent to state highway–had sulphation rate 1.16 mg SO3/100 cm2/day whereas for Nakoda 1.23 mg SO3/100 cm2/day which was adjacent to local road. From the results it was evident that sulphation rate was more in upwind direction as compared with downwind direction may be due to presence of pulp and paper mill. Industrial activities in Chandrapur industrial cluster contributes significant sulphur emissions from pulp and paper mill, super thermal power station where coal is used, ore smelting, number of cement industries, emissions from diesel driven heavy and light motor vehicles along with domestic coal burning. As wind progresses from upwind to downwind direction sulphur concentration was reduced due to dilution, dispersion and transportation, which result into reduced sulphation rate in downwind direction. INTERNATIONAL JOURNAL OF ENVIRONMENT Volume-5, Issue-2, Mar-May 2016 Page :15-25